Purchase list and recipe mobile application - Chai, Melvin Wen Da (2025)
Recipe system is a system that allow user to simplify in cooking process and meal planning. It will provide a various type of recipe for different tastes and dietary needs, including vegetarian, vegan and others. Each recipe includes step-by-step instructions in text form and photo so the user can easily follow. This system also has the purchase list function. It will calculate the estimated amount of ingredient needed for one week. This function will be based on the number of servings to calculate. It will recommend recipes that are based on the remaining ingredient so users can reduce the amount of food wasted. When the ingredient of the remaining ingredient list matches with the ingredient needed, the system will automatically mark the ingredient already had in the ingredient needed list. Furthermore, this system also had one function which is to display the nutrition of one week meal plan. This function helps user easily to plan a variety of meals while ensuring a balanced diet. Each recipe provided detailed nutritional information like the amount of protein, carbohydrates and other nutritional information. Users can be based on their body health to set up a meal plan. This system will be developed as a mobile application, and the user can be easier to use because mobile applications will provide a complete graphic interface. Users also can use the application anywhere and anytime.